SISTEM INFORMASI PENJUALAN ANEKA MAKANAN RINGAN BERBASIS WEBSITE DI PEKON SUKOHARJO 3 BARAT - Mardeli, Iis; Muanam, Sahrul; Muslihudin, Muhamad (STMIK Pringsewu, 2025)
With the rapid advancement of computer information technology, various innovations have emerged in information presentation to meet sales needs, especially in the micro, small, and medium enterprises (UMKM) sector. In Sukoharjo 3 village, there are around 38 UMKMs that play an important role in the local economy, but there is no website providing information about the sale of various snacks. To address this issue, this research aims to develop a web-based sales system for snack businesses in the area. The research uses the Waterfall method, which includes stages such as requirement analysis, system design, programming, testing, implementation, and maintenance. The system design involves use case diagrams, class diagrams, and activity diagrams. The results show that this sales information system can monitor the availability of goods and manage the incoming and outgoing goods information. This system not only addresses sales process issues but also helps increase sales volume and expand market reach. The implementation of this web-based sales system is expected to optimize the sales process and provide a more satisfying shopping experience for consumers.